Surgeons Do Not Listen: Evaluation of Compliance with Antimicrobial Stewardship Program Recommendations. Issue 12 (December 2013) - Duane, Therese M.; Zuo, Jessica X.; Wolfe, Luke G.; Bearman, Gonzalo; Edmond, Michael B.; Lee, Kimberly; Cooksey, Laurie; Stevens, Michael P.
The purpose of this study was to determine if there are differences in interventions (int) required and compliance (comp) to recommendations (rec) by medical and surgical services as determined by an antimicrobial stewardship program (ASP). Concurrently collected ASP data from January 2008 through May 2011 were evaluated to determine number of int required and response to int. Results for medical (med) and surgical (surg) services were compared. There were 2322 int, of which 1108 were for med and 1214 were for surg. Recs were as follows: 242 appropriate coverage (AC) med versus 212 AC surg and 866 selective pressure (SP) med and 1002 SP surg. Comp with recs was higher for med: AC: 90.5 per cent (219 of 242) med versus 82.1 per cent (174 of 212) surg ( P = 0.0086) and SP: 81.1 per cent (702 of 866) med versus 69.5 per cent (696 of 1002) surg ( P < 0.0001). Overall surgical comp with ASP recs was better for AC than for SP. Moreover, less than half (seven of 15) of the surgical subspecialties demonstrated a comp of 75 per cent or greater with SP recs with only one-fifth having a comp over 80 per cent. Surgical services demonstrate poor compliance with ASP recommendations; this is especially true for interventions targeting selective pressure. By identifying services that are less compliant, programs can target their educational efforts to improve outcomes.